Forecasting Market Capitalization on The Jakarta Islamic Index using The Arima Method - Zul Ihsan Mu'arrif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze and forecast the market capitalization of the Jakarta Islamic Index through 2028 using the Autoregressive Integrated Moving Average (ARIMA) methodology. By applying ARIMA analysis to historical data spanning from 2011 to 2024, this study specifically identifies factors such as increased investor interest, continuous innovation in Islamic financial products, and stable macroeconomic conditions as primary drivers behind the dynamic growth of the Islamic capital market. The findings of this research reveal a significant positive growth trend in the Islamic capital market, offering valuable insights and extensive practical implications for investors, market analysts, and policymakers. This information is crucial as it can be utilized to formulate more effective investment strategies and design policies that support the sustainable growth of the Islamic capital market. Through meticulous application of the ARIMA model and in-depth analysis of influencing factors, this study contributes new insights to the Islamic finance literature, enhancing understanding of how various market dynamics and economic factors impact the Islamic capital market in Indonesia while also offering practical recommendations for leveraging this market's growth potential.